Media Pembelajaran Interaktif pada Pendidikan Teknik Penerbangan - Nurfikri, Aditia; Firmanda, Ardiman (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
The advancement of Virtual Reality (VR) technology has significantly contributed to the field of education, particularly in vocational learning environments. This study aims to develop and evaluate FLIGHTECH IMMERSION, an interactive learning application based on VR technology integrated with hand tracking, designed to help students explore aircraft components virtually. The application was developed using the Multimedia Development Life Cycle (MDLC) method, consisting of six stages: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. Functional testing was conducted using the black-box testing method, while user evaluation employed a quantitative descriptive approach through a questionnaire distributed to 32 students of the Aircraft Maintenance Engineering Program at Batam State Polytechnic. The results showed an average user satisfaction score of 4.42, classified as "Very Feasible". These findings indicate that FLIGHTECH IMMERSION can serve as an innovative and effective educational medium for immersive learning in the field of aviation technology.